THE VIRTUES OF THE REPUBLIC: THE BENEFITS OF THE NARRATIVE REPUBLIC (Andamios, Revista de Investigación Social, 2007)
The republican political project has been the occasion of a renewed interest in contemporary political theory, as a preferred alternative to the undesired consequences of some applications of liberalism. In this paper I explore the contrasts between the two traditions as a jumping-off point to analyze Charles Taylor’s and Quentin Skinner’s understanding of republicanism. Moving beyond their differences, I show that both thinkers share the idea that republican citizenship does not conflict with those liberal values that are still worthy of being defended. Finally, I provide some thoughts on the desirability of rehabilitating the republican narrative in the Latin American context.
Keywords: Republicanism; liberalism; citizenship; self-government; civic virtue